Protocol for high-throughput reservoir quantification across global HIV subtypes using a cross-subtype intact proviral DNA assay - Carolyn S. Fish; Noah A.J. Cassidy; Claire N. Levy; Sean M. Hughes; Keith R. Jerome; Julie Overbaugh; Florian Hladik; Dara A. Lehman (STAR Protocols, 2022)
Summary: The cross-subtype intact proviral DNA assay (CS-IPDA) is a high-throughput method to quantify HIV reservoir size in populations infected with any of the dominant global HIV-1 subtypes. Our protocol includes genomic DNA isolation optimized to minimize DNA shearing, a reference droplet digital PCR (ddPCR) assay to quantify T cells and assess DNA shearing, and a multiplex ddPCR targeting three distinct regions across the HIV genome to quantify intact proviruses as an estimate of replication-competent proviruses in the reservoir.For complete details on the use and execution of this protocol, please refer to Cassidy et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.